2023
DOI: 10.3390/cells12050805
|View full text |Cite
|
Sign up to set email alerts
|

LIM Kinases, LIMK1 and LIMK2, Are Crucial Node Actors of the Cell Fate: Molecular to Pathological Features

Abstract: LIM kinase 1 (LIMK1) and LIM kinase 2 (LIMK2) are serine/threonine and tyrosine kinases and the only two members of the LIM kinase family. They play a crucial role in the regulation of cytoskeleton dynamics by controlling actin filaments and microtubule turnover, especially through the phosphorylation of cofilin, an actin depolymerising factor. Thus, they are involved in many biological processes, such as cell cycle, cell migration, and neuronal differentiation. Consequently, they are also part of numerous pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 246 publications
1
4
0
Order By: Relevance
“…7I). Cofilin, a substrate of LIMK1, can be phosphorylated to p-cofilin, which is involved in the formation of F-actin during neuronal differentiation (Yang et al 1998;Ben Zablah et al 2021;Villalonga et al 2023). Consistently, the mean F-actin intensity decreased significantly after knockdown of either the EIciLIMK1 or LIMK1 mRNA (Fig.…”
Section: Regulation Of Cirs and Eicirnas Has Functional Roles In Neur...supporting
confidence: 62%
“…7I). Cofilin, a substrate of LIMK1, can be phosphorylated to p-cofilin, which is involved in the formation of F-actin during neuronal differentiation (Yang et al 1998;Ben Zablah et al 2021;Villalonga et al 2023). Consistently, the mean F-actin intensity decreased significantly after knockdown of either the EIciLIMK1 or LIMK1 mRNA (Fig.…”
Section: Regulation Of Cirs and Eicirnas Has Functional Roles In Neur...supporting
confidence: 62%
“…The top four targets that are significantly upregulated are: CCNG1 (Cyclin G1) and PHLPP2 which have both been shown to induce cell cycle arrest (5761), GOLM1 (Golgi membrane protein 1, also known as GP73) which is a validated miR-27 target that is emerging as a key regulator of IL-6 also linked to innate immunity and RSV infection (62–66) and LIMK1 (LIM domain kinase 1, Fig 4E), a serine/threonine-protein kinase involved in remodelling of the cytoskeleton. LIMK1 has been shown to be an important host factor for many viral life cycles, including HIV, HSV-1, and Influenza virus (6771) and LIMK1 inhibitors are currently explored as broad-spectrum antiviral drugs (72). These data suggest that the miR-27 HC targets most susceptible to miRNA inhibition in lung epithelial cells are highly relevant to viral infection.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that LIMK1 can promote the expression of actin in cervical cancer cells. Actin is an important part of the cytoskeleton, involved in cell movement, pseudopodia formation, and invasion [ 23 ]. Our results suggest that LIMK1 can promote the invasion and metastasis of cervical cancer cells by regulating the expression of actin.…”
Section: Discussionmentioning
confidence: 99%